Viability of probiotic bacteria in tropical mango juice and the resistance of the strains to gastrointestinal conditions simulated in vitro - Furtado, Lívia Ladeira; Martins, Maurilio Lopes; Ramos, Afonso Mota; Silva, Roselir Ribeiro da; Leite Junior, Bruno Ricardo de Castro; Martins, Eliane Maurício Furtado (Semina: Ciências Agrárias, 2019)
This study evaluated the viability of Lactobacillus acidophilus La-05, Lactobacillus plantarum LP299v and Lactobacillus rhamnosus GG in tropical mango juice, the resistance of the strains to gastrointestinal conditions simulated in vitro and the microbiological, physicochemical and sensory characteristics of the products obtained. The viabilities of L. rhamnosus GG and L. plantarum LP299v were greater than 7.96 log CFU mL-1 and 7.74 log CFU mL-1, respectively, during the 28 days of storage at 8 Â°C. However, there was a reduction (p < 0.05) in the viability of L. acidophilus La-5 after 21 days of storage, with counts of 3.81 log UFC mL-1. The parameters of pH, total soluble solids, luminosity (L*) and the color coordinates, a* and b*, did not differ between the treatments. However, the pH and acidity varied during the storage time, probably due to the fermentative action of the microorganisms. For the in vitro gastrointestinal resistance test, there was a difference in the gastric phase for enteric phases I and II. The mean viability of the microorganisms in the gastric phase was 5.11 log CFU mL-1, decreasing to 4.02 and 3.97 log CFU mL-1 in enteric phases I and II, respectively. Juices containing L. rhamnosus GG and L. plantarum LP299 were evaluated sensorially, presenting good acceptability. The results suggest that the tropical mango juice was a good carrier matrix for L. rhamnosus GG and L. plantarum LP 299v, being well accepted and therefore an alternative for populations with dietary restrictions.